2015
DOI: 10.1186/s12906-016-1010-7
|View full text |Cite
|
Sign up to set email alerts
|

Preference and willingness to pay for traditional medicine services in rural ethnic minority community in Vietnam

Abstract: BackgroundTraditional medicine (TM) still plays an important role in a number of health care systems around the world, especially across Asian and African countries. In Vietnam, however, little is known about preference for traditional medicine use. This study assessed the prevalence of use, preference, satisfaction, and willingness to pay for TM services amongst rural ethnic minority community.MethodsA cross-sectional survey in three provinces in the North and South of Vietnam.ResultsThe results showed a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Broadly speaking traditional medicine use is common amongst people of all levels of education, community size and place of residence. This level of traditional medicine use is comparable with other studies from the region and elsewhere [11][12][13]. Research by Suswardany in neighbouring Indonesia found that respondents used traditional medicine for general health/common illness purposes every day [13].…”
Section: Discussionsupporting
confidence: 85%
“…Broadly speaking traditional medicine use is common amongst people of all levels of education, community size and place of residence. This level of traditional medicine use is comparable with other studies from the region and elsewhere [11][12][13]. Research by Suswardany in neighbouring Indonesia found that respondents used traditional medicine for general health/common illness purposes every day [13].…”
Section: Discussionsupporting
confidence: 85%
“…Revealing the association results, study participants who had visited THPs before were found to have significant positive attitude, preference of TM as a primary treatment of choice, and were more likely to use TM in the future compared to those who had never visited THPs. Perceived effectiveness of TM [ 5 , 10 , 13 ], satisfaction level [ 12 ], and minimum treatment complications encountered could have possibly motivated the respondents who had used TM to further visit THPs. Rurality [ 27 ], educational level [ 22 , 26 ], marital status [ 22 ], and income [ 22 ] were found to influence subsequent T&CM practices in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, there has also been a global surge in popularity and use of T&CM in both developed and developing countries [ 5 – 9 ]. In which, cultural acceptability [ 2 , 5 , 10 , 11 ], perceived efficacy [ 7 , 12 ], affordability [ 2 , 13 , 14 ], accessibility [ 7 ], and psychological comfort [ 5 ] of TM along with poor access to modern health services [ 5 , 7 , 12 ] and shortage of conventional health professionals [ 7 ], are among the main factors impacting the high degree of utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of the product was vital for patients to accurately estimate their WTP for the product. 32 , 33 …”
Section: Methodsmentioning
confidence: 99%